Lithic Industry as an Indicator of Ceramic Diffusion in the Early Neolithic of West Africa: A Case Study at Ounjougou - (:unkn) unknown (My University, 2012)
Ounjougou (Dogon Country, Mali) is now known for the discovery there of pottery dating to the first half of the 10th millennium cal BC, which is among the earliest evidence of the use of ceramics in Africa. While our understanding of early African ceramics is becoming well developed, certain other evidence associated with the first manifestations of the African Neolithic are still poorly understood, including notably the lithic industries. On the basis of technological and typological analyses of the lithic assemblage associated with the Ounjougou pottery, we will show that these materials also express profound behavioral changes within cultural groups of this period, and indeed they help clarify processes for the spread of ceramics. For these reasons lithics are extremely important for understanding this period of great cultural change and should not be neglected. Technological and typological data collected during the analysis have been used to propose an original taphonomic approach and to test in this way the coherence of the assemblage. Comparisons with Early Holocene industries in the Saharan zone (Temet, Tagalagal, Adrar Bous 10, etc.) provide new elements of consideration regarding the cultural context of the appearance of pottery, and enable us to proposea scenario for the adoption of technological innovations marking the beginning of the Holocene, from sub-Saharan West Africa toward the central Sahara. The lithic industries are seen as a valuable means of clarifying the cultural context and processes of the appearance and spread of pottery in this region from the first half of the 10th millennium cal BC to the middle of the 9th millennium cal BC.
Keywords: African Research